Social Networks and Labor Market Inequality between Ethnicities and Races - Ott Toomet; Marco van der Leij; Meredith Rolfe (Tinbergen Institute, 2012)
This paper analyzes the relationship between unexplained racial/ethnic wage differentials on the one hand and social network segregation, as measured by inbreeding homophily, on the other hand. Our analysis is based on both U.S. and Estonian surveys, supplemented with Estonian telephone communication data. In case of Estonia we consider the regional variation in economic performance of the Russian minority, and in the U.S. case we consider the regional variation in black-white differentials. Our analysis finds a strong relationship between the size of the differential and network segregation: regions with more segregated social networks exhibit larger unexplained wage gaps.
urn:nbn:nl:ui:29-441459
Keywords: J71; J31; Z13; 330; social networks; wage differential; homophily; segregation; race; minorities; Minderheit; Soziales Netzwerk; Lohnstruktur; Rasse; USA; Estland